Analisis Pengendalian Persediaan TBS Dengan Metode EOQ (Economic Order Quantity) di PT. Agrindo Indah Perkasa Tambang Baru - Agus Topo Subekti (Jurnal INOVATOR, 2018)
PT. Agrindo Indah Perkasa located in the new mining village of Meranginyang Regency produces CPO so far in controlling the supply of its main raw material, namely FFB, which only receives from farmers around because PT. AIP does not yet have its own garden. So that the efficiency of ordering costs and storage costs for raw materials are not optimal. This research was conducted to find out the raw material inventory control system applied by the company, the efficiency of inventory control of raw materials obtained, the analysis of Economic Order Quantity (EOQ) and the extent to which the Economic Order Quantity (EOQ) method can streamline the cost of controlling raw material inventories. is a descriptive method and method of verification method. Based on the results of the study using the Economic Order Quantity (EOQ) method, the number of orders that are economical is 303 tons / month, with the order frequency of 14 times / month. The point of re-ordering was done when the supply of fuel was 1357 tons. The total cost of inventory using company calculations of Rp. 66,300,000, while using the Economic Order Quantity (EOQ) method the company only issues a total inventory cost of Rp. 26,346,428. By using the company EOQ method can save the total inventory cost of Rp. 39,953,572 or 39.74% ...